Penerapan Algoritma Apriori Untuk Menemukan Pola Peminjaman Buku Di Perpustakaan (Studi Kasus: Sekolah Menengah Atas Negeri 2 Cepu) - Retno Wahyusari (SIMETRIS, 2022)
The library is a means of providing information, sources of knowledge and means of supporting teaching and learning activities for users to obtain the desired information. Cepu Public High School 2 library has a collection of books ranging from subject books to other types of books around 600 copies. More than 280 new students with all students ranging from 10th to 12th grade around 750 students, therefore with this increase in number of students the library is also required to increase its book collection to support the activities of its students. Cepu Public High School 2 library is more than 10 visitors per visit, one of the activities in the library is borrowing books. Every year the library staff reports on books that have been borrowed by students, about 100 books lending transactions per year. The average student in publishing more than one book, they buy books based on the relevance of the subject matter. Students in the search for books that have a connection takes quite a long time, this is related to the placement of books that are not based on the relevance of the textbook. Linkages between books can be identified by gathering information by collecting lending data sets. Extracting the linkage information between book items is known as the association rule method. The rule association method in this study uses the Apriori algorithm to provide book placement recommendations. Apriori algortiam selection because Apriori algorithm is the most established algorithm in the rules of association. The results of the research conducted resulted in 3 rules of association rules with a minimum support value of 20% with a minimum trust value of 50% and 70% obtained the highest value of the confidence of 78% and 47% support if using books 500-599 books will be purchased 300-499.